Getting Stuck in the Blues: Persistence of Mental Health Problems in Australia - John R. Roy; Stefanie Schurer (Institute for the Study of Labor (IZA), 2013)
Do episodes of mental health problems cause future mental health problems, and if yes, how strong are these dynamics? We quantify the degree of persistence in mental health problems using nationally-representative, longitudinal data from Australia and system GMM-IV and correlated random effects approaches are applied to separate true from spurious state dependence. Our results suggest only a moderate degree of persistence in mental health problems when assuming that persistence is constant across the mental health distribution once individual-specific heterogeneity is accounted for. However, individuals who fell once below a threshold that indicates an episode of depression are up to five times more likely to experience such a low score again a year later, indicating a strong element of state dependence in depression. Low income is a strong risk factor in state dependence for both men and women, which has important policy implications.
Keywords: I14; C23; 330; mental health; depression and anxiety; dynamic panel data models; GMM-IV; HILDA